Property-Tuneable Microgels Fabricated by Using Flow-Focusing Microfluidic Geometry for Bioactive Agent Delivery - Wing-Fu Lai; Wing-Tak Wong (MDPI AG, 2021)
Gelatine methacryloyl (GM) shows high biocompatibility and is extensively used in tissue engineering; however, few works have explored the use of GM in bioactive agent delivery. This study adopts a microfluidic approach involving the use of flow-focusing microfluidic geometry for microgel fabrication. This approach generates highly monodisperse microgels whose size can be tuned by altering various fabrication conditions (including the concentration of the gel-forming solution and the flow rates of different phases). By using tetracycline hydrochloride as a model agent, the fabricated microgels enable prolonged agent release, with the encapsulation efficiency being around 30-40% depending on the concentration of the gel-forming solution. Along with their negligible cytotoxicity, our microgels show the potential to serve as carriers of bioactive agents for food and pharmaceutical applications.